Pengaruh Tingkat Interaksi Sosial dalam Pembelajaran IPA Terhadap Motivasi Belajar Peserta Didik Kelas VII SMP Negeri 1 Binamu (Indo-MathEdu Intellectuals Journal, 2025)
This study used a quantitative approach with an ex-post facto method. The research population consisted of all 177 seventh-grade students at SMP Negeri 1 Binamu. From this population, a sample of 63 students was taken using simple random sampling so that each student had an equal chance of being selected. The data collection instruments consisted of a questionnaire to measure the level of social interaction and learning motivation of students, as well as observation sheets to reinforce field data. Data analysis was carried out in several stages, namely a normality test to ensure data distribution, a linearity test to see the relationship between variables, and a simple regression test to determine the extent of the influence of social interaction on student learning motivation. The analysis results show that the average value of social interaction is in the fairly good category, while student learning motivation is also moderate. Based on a simple regression test, a t-value of 1.048 with a significance of 0.000 < 0.05 was obtained. These results indicate that social interaction has a significant effect on student learning motivation. The contribution of social interaction to learning motivation is 47.619%. This means that almost half of the variation in student learning motivation can be explained by the level of social interaction that occurs in science learning, while the rest is influenced by other factors outside this study